Strangeness Enhancement at LHC Energies Using the Thermal Model and EPOSLHC Event Generator - Mahmoud Hanafy; Omnia S. A. Qandil; Asmaa G. Shalaby (Advances in High Energy Physics)
The strangeness enhancement signature of QGP formation at LHC energies is carefully tackled in the present study. Based on HRG, the particle ratios of mainly strange and multistrange particles are studied at energies from lower s~0.001 up to 13 TeV. The strangeness enhancement clearly appeared at more high energies, and the ratios are confronted to the available experimental data. The particle ratios are also studied using the Cosmic Ray Monte Carlo (CRMC) interface model with its two different event generators, namely, EPOS 1.99 and EPOSlhc, which show a good agreement with the model calculations at the whole range of the energy. We utilize them to produce some particles ratios. EPOS 1.99 is used to estimate particle ratios at lower energies from AGS up to the Relativistic Heavy Ion Collider (RHIC) while EPOSlhc is used at LHC energies. The production of kaons and lambda particles is studied in terms of the mean multiplicity in p-p collisions at energies ranging from 4 to 26 GeV. We find that both HRG model and the used event generators, EPOS 1.99 and EPOSlhc, can describe the particle ratios very well. Additionally, the freeze-out parameters are estimated for different collision systems, such as p-p and Pb-Pb, at LHC energies using both models.